Learning design for statistics materials using the context of traditional market assisted by interactive videos - Dina Lita Sari; Farida Nursyahidah (Universitas Hamzanwadi, 2022)
Statistics is one of the mathematics subjects that can be useful in everyday life, especially data presentation material. However, many students still have difficulty understanding the data presentation material. So, it is necessary to design learning using the appropriate context and approach in learning data presentation material. Therefore, the researcher aims to determine student learning trajectories in understanding the presentation of statistical data using traditional markets as a context in the learning process using the Indonesian Realistic Mathematics Education (PMRI) approach assisted by interactive video. The research method used is the design research, which has three stages: the preliminary design stage, the experimental design stage (pilot experiment and teaching experiment), and the retrospective analysis stage. This study indicates that the learning trajectory obtained can help students understand the concept of data presentation material. The learning trajectory uses traditional market contexts and consists of 5 activities, namely: observing traditional market context learning videos and determining data, presenting data in the form of various tables, presenting data in the form of bar charts, presenting data in a line chart, presenting data in the form of pie charts and solving a contextual problem. Furthermore, the results of this study are expected to be an inspiration in learning using the context of everyday life.